The relation between snoring and smoking, body mass index, age, alcohol consumption and respiratory symptoms - F. Kauffmann; I. Annesi; Françoise Neukirch; M-P Oryszczyn; Annick Alpérovitch (1989)
Potential risk factors for snoring were studied in a population of 457 middle-aged men. Eversnoring was reported by 60% of the men and snoring with an age of onset before or equal to 20 years by 13%. Eversnoring was significantly related to older age, higher body mass index and smoking habits. Alcohol consumption, estimated by questionnaire and gamma-glutamyl transpeptidase was unrelated to a history of snoring. Logistic regression showed that snoring was independently associated with age, body mass index and smoking habits. An exposure-effect relationship clearly appeared between tobacco consumption and snoring. After adjustment for smoking habits, none of the upper or lower respiratory symptoms was significantly related to snoring.